772 Perspectives on Simulation as an Assessment Tool in Surgical Training: A Qualitative Study of Key Stakeholders. (19th August 2022) - Toale, C; Morris, M; O Kavanagh, D
Abstract: Aim: The perspectives of the wider surgical community toward simulation-based assessment (SBA) in training is a gap in the literature. This study aims to generate a conceptual framework regarding the acceptable use of SBA in surgical training, through the perceptions and experiences of a broad range of stakeholders. Method: A sequential transformative qualitative methods approach employing constructivist grounded theory was used. Ten semi-structured interviews were conducted representatives from identified key stakeholder groups; executive management, risk management, a practicing surgeon, an anaesthesiologist, a theatre-nursing representative, a representative from simulation, a patient, a medical student, a junior surgical trainee and a senior surgical trainee. interview transcripts underwent content analysis using NVIVO software (NVIVO 12, QSR International). Results: Four themes emerged: the 'need' for SBA, the concept of a 'minimum standard', the 'optimum design' of an SBA framework, and 'fairness'. SBA is a potential solution to challenges in the current training environment. It emerged that it should not replace trainer judgement but could ensure that trainees meet a minimum operative competency standard. SBA should be used to identify underperforming trainees early in training, to provide remediation. The application of SBA in high stakes settings such as trainee selection, autonomy granting, and end-of training certification has perceived benefits over current assessment methods. Conclusions: This study generates a conceptual framework regarding the acceptable use of simulation as an assessment tool in surgical training, including perspectives from a broad range of stakeholders. Findings can inform the development of simulation-based assessment curricula in surgical training.